Fatigue crack propagation in turbine disks of EI698 superalloy - A.A. Shanyavskiy (Fracture and Structural Integrity)
In-service fatigue cracking of turbine disks of EI698 superalloy is discussed based on crack growth analyses. In the bolt joint for disks to shaft connecting there is high level of stress-state, which directed to earlier in-disks fatigue crack origination in low-cycle-fatigue regime. Fracture surface pattern such as fatigue striations were used for their spacing measurement and crack growth duration estimating. Developed disk tests on a special bench by the equivalent program to in-service cyclic loads have allowed discovering one-to-one correlation between fatigue striation spacing and crack increment in one flight. Number of fatigue striations and beach-marks calculations permitted to estimate crack growth period for the different stages of in-service disks cracking. Equivalent stress level for in-service cracked disks was calculated and compared with stress-level intested disks under stress equivalent program to in-service operated cyclic loads. Based on this result nondestructive inspection intervals were discussed and recommended for in-service disks in dependence on number of their flights at the moment of developed inspection to exclude in-flight disks fast fracture.